High-strength anti-crack foam concrete
By using modified bamboo fiber-carbon nanotube composite materials in foam concrete, a stable three-dimensional network structure is formed, which solves the problem of insufficient compressive flexural strength and crack resistance of foam concrete, and achieves foam concrete with high strength, low cracks and good thermal insulation properties.
Patent Information
- Application Number
- CN202411536353.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing foam concrete has shortcomings in compressive flexural strength and crack resistance, and is prone to cracking and leakage, which limits its promotion and application.
Modified bamboo fiber-carbon nanotube composite material is used as the fiber reinforcement agent, and the bamboo fiber is modified and processed and connected with the carbon nanotubes to form a stable three-dimensional network structure. Combined with suitable foam stabilizers and other raw materials, the raw material ratio is optimized to prepare high-strength crack-resistant foam concrete.
The compressive strength, crack resistance and thermal insulation properties of foam concrete are significantly improved, the drying shrinkage rate is reduced, the pores and cracks are reduced, and the durability is improved, the compatibility and adhesion between the fiber and the cement matrix is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to high-strength crack-resistant foamed concrete. Background Art
[0002] Foamed concrete is a special type of building material with micropores. It has attracted much attention due to its advantages such as self-leveling, low thermal conductivity, less raw materials required and light weight, as well as excellent properties such as light weight, environmental protection, sound absorption and fire resistance. It is widely used in exterior wall and roof insulation of residential buildings, tunnel filling and pipe filling of underground projects, as well as sculptures and decorative elements in the decoration field. Its flexibility and versatility make it a popular material choice in the construction field.
[0003] As we all know, foamed concrete has the characteristics of high porosity and strong pore connectivity, which makes it have good insulation and heat insulation properties. However, it also leads to relatively low compressive and flexural strength, high water content, and easy cracking and leakage, which seriously hinders the promotion and application of foamed concrete. Therefore, the research on the improvement of foamed concrete performance has become a hot research topic in the field of building materials. At present, the specific measures to improve the performance of foamed concrete can be divided into three categories: one is to change the foaming method to change the internal control structure of foamed concrete and fill and reinforce the voids; the second is to add fibers to inhibit the shrinkage and cracking of foamed concrete; the third is to add mineral admixtures such as fly ash, slag, and silica fume to improve the pore structure of foamed concrete by using their volcanic ash effect and micro-aggregate filling effect. A large number of research results show that adding an appropriate amount of fiber (organic fiber or inorganic fiber) as a reinforcing agent during the preparation of foamed concrete can improve the comprehensive performance of foamed concrete. However, the addition of a single type of fiber has limited effect on the performance improvement of foamed concrete. How to prepare a foamed concrete with better comprehensive performance has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength crack-resistant foamed concrete. The prepared foamed concrete has excellent compressive strength, crack resistance and good thermal insulation performance.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A high-strength crack-resistant foamed concrete is made from the following raw materials in parts by weight: 200-300 parts of cement, 10-20 parts of silica fume, 10-20 parts of fly ash, 1-2 parts of foaming agent, 5-15 parts of fine aggregate, 1-3 parts of foam stabilizer, 5-10 parts of modified bamboo fiber-carbon nanotube composite material, 0.5-1 part of water reducer, and 120-130 parts of water; The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing the carbon nanotubes by ultrasonication for 30 minutes to obtain a carbon nanotube suspension; (3) Bamboo fiber and 0.2 mol / L CaCl 2 The solutions were mixed and stirred at 400 r / min for a period of time. After the reaction was completed, equal amounts of Na 2 CO 3 solution, dispersant EDTA-2Na, continue stirring at 300r / min for 25min, after the reaction is finished, rinse with a 200-mesh nylon net under tap water until there are no obvious particles in the suspension, air dry, and obtain modified bamboo fiber; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 min, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 min, taking it out and drying it to obtain the pretreated modified bamboo fiber; (5) The pretreated modified bamboo fiber was added to the prepared carbon nanotube suspension and magnetically stirred for 12 h. After filtration, the modified bamboo fiber-carbon nanotube composite material was obtained.
[0006] Preferably, the mass ratio of distilled water, silane coupling agent and anhydrous ethanol in the silane coupling agent solution is 1:5:50, and the silane coupling agent is KH550.
[0007] Preferably, the concentration of carbon nanotubes in the carbon nanotube suspension is 0.5 wt %.
[0008] Preferably, in step (3), the bamboo fiber and CaCl 2 The dosage ratio of the solution is 1g:50ml, and the stirring reaction time is 30min.
[0009] Preferably, in step (3), EDTA-2Na and CaCl 2 The dosage ratio of the solution is 0.01g:1ml.
[0010] Preferably, the concentration of the stearic acid ethanol solution is 2wt%, and the concentration of the sodium hydroxide solution is 0.5mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1g:20ml:20ml.
[0011] Preferably, the usage ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1g:50ml.
[0012] Preferably, the foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0013] Preferably, the foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0014] Preferably, the cement is ordinary Portland cement P·O42.5; and the water reducer is a polycarboxylate water reducer.
[0015] The preparation method of the high-strength crack-resistant foamed concrete of the present invention is: (1) preparing a modified bamboo fiber-carbon nanotube composite material according to the above steps; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, modified bamboo fiber-carbon nanotube composite material, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, add the foam stabilizer, and continue to stir the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0016] Existing studies have shown that adding an appropriate amount of fiber as a reinforcing material during the preparation of foamed concrete can improve the comprehensive performance of foamed concrete, and the type, output and method of adding fiber will have an important impact on foamed concrete. The present invention prepares a modified bamboo fiber-carbon nanotube composite material by a specific method, which first uses nano-calcium carbonate to modify bamboo fiber, and then connects the surface of the modified bamboo fiber with carbon nanotubes through a silane coupling agent after surface treatment, and chemically bonds the silicon hydroxyl group with a large number of active hydroxyl groups on the surface of carbon nanotube molecules and the active hydroxyl groups on the surface of the modified bamboo fiber to form a modified bamboo fiber-carbon nanotube composite material. The fiber composite material forms a stable three-dimensional network structure inside the concrete, promoting the uniform distribution of internal bubbles, which effectively reduces the drying shrinkage of the foamed concrete and improves the compressive strength, crack resistance and thermal insulation performance of the foamed concrete; on the other hand, since the modified bamboo fiber-carbon nanotube composite material contains bamboo fiber modified with nano-calcium carbonate, the nano-calcium carbonate therein can promote cement hydration reaction, refine the crystal form and improve the interface structure of the concrete, which helps to reduce the pores and cracks in the concrete, reduce the permeability and water absorption of the concrete, and further improve the durability of the concrete. At the same time, the fiber composite material prepared by the present invention improves the compatibility and bonding force between the fiber material and the cement matrix, and further improves the anti-cracking performance of the concrete.
[0017] The foam stabilizer used in the present invention is composed of dodecyl dimethylamine oxide and polyacrylamide in a mass ratio of 1:1. The adhesive thickening property of polyacrylamide can enhance the viscosity of concrete, making the bubbles more stable and not easy to break; while the foaming and foam stabilizing properties of dodecyl dimethylamine oxide can further increase the number of bubbles in concrete and improve the stability of bubbles. The two work together to achieve a good foam stabilizing effect, and at the same time, they also work synergistically with the modified bamboo fiber-carbon nanotube composite material used in the present invention to make the closed pores in the foam concrete uniform in distribution and size, reduce the probability of compression cracking of the foam concrete, and thus improve the comprehensive performance of the concrete.
[0018] The present invention adds silica ash and fly ash at the same time, and the active SiO 2 It reacts with calcium hydroxide produced by cement hydration to increase the volume of CSH gel in cement paste, reduce porosity, improve pore structure, and thus improve the strength of concrete; while the active part SiO 2 and Al 2 O 3 Ca(OH) generated by cement hydration 2 The reaction generates a large amount of hydrated silica gel, which can fill the gaps and destroy the Ca(OH) 2 The preferred orientation arrangement greatly improves the interface area and promotes the growth of the later strength of concrete.
[0019] The beneficial effects of the present invention are as follows: The foamed concrete made by using specially modified bamboo fiber-carbon nanotube composite material as fiber reinforcement, selecting suitable foam stabilizers and other raw materials, and optimizing the raw material ratio has excellent compressive strength, flexural strength, crack resistance and thermal insulation performance, good comprehensive performance, and extremely good market application prospects. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto. The raw materials used in the present invention are commercially available unless otherwise specified.
[0021] Example 1 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 200 parts of cement, 10 parts of silica fume, 10 parts of fly ash, 1 part of foaming agent, 5 parts of fine aggregate, 1 part of foam stabilizer, 5 parts of modified bamboo fiber-carbon nanotube composite material, 0.5 part of water reducer, and 120 parts of water.
[0022] The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0023] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0024] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0025] The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing by ultrasonication for 30 min to obtain a carbon nanotube suspension with a concentration of 0.5 wt%; (3) Bamboo fiber and 0.2 mol / L CaCl 2 The solutions were mixed in a ratio of 1g:50ml, stirred at 400r / min for 30min, and then added with equal amounts of Na 2 CO 3 solution, dispersant EDTA-2Na, continue stirring at 300r / min for 25min, after the reaction is completed, rinse with a 200-mesh nylon net under tap water until there are no obvious particles in the suspension, air dry, and obtain modified bamboo fiber; EDTA-2Na and CaCl 2 The dosage ratio of the solution is 0.01g:1ml; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 minutes, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 minutes, taking it out and drying it to obtain pretreated modified bamboo fiber; the concentration of the stearic acid ethanol solution is 2wt%, and the concentration of the sodium hydroxide solution is 0.5mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1g:20ml:20ml; (5) Add the pretreated modified bamboo fiber to the prepared carbon nanotube suspension and stir under magnetic force for 12 hours, and obtain the modified bamboo fiber-carbon nanotube composite material after filtration. The amount ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1g:50ml.
[0026] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) preparing a modified bamboo fiber-carbon nanotube composite material according to the above steps; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, modified bamboo fiber-carbon nanotube composite material, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, add the foam stabilizer, and continue to stir the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0027] Example 2 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 250 parts of cement, 15 parts of silica fume, 15 parts of fly ash, 1.5 parts of foaming agent, 10 parts of fine aggregate, 2 parts of foam stabilizer, 8 parts of modified bamboo fiber-carbon nanotube composite material, 0.8 parts of water reducer and 125 parts of water.
[0028] The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0029] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0030] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0031] The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing by ultrasonication for 30 min to obtain a carbon nanotube suspension with a concentration of 0.5 wt%; (3) Bamboo fiber and 0.2 mol / L CaCl 2 The solutions were mixed in a ratio of 1g:50ml, stirred at 400r / min for 30min, and then added with equal amounts of Na 2 CO 3 solution, dispersant EDTA-2Na, continue stirring at 300r / min for 25min, after the reaction is completed, rinse with a 200-mesh nylon net under tap water until there are no obvious particles in the suspension, air dry, and obtain modified bamboo fiber; EDTA-2Na and CaCl 2 The dosage ratio of the solution is 0.01g:1ml; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 minutes, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 minutes, taking it out and drying it to obtain pretreated modified bamboo fiber; the concentration of the stearic acid ethanol solution is 2wt%, and the concentration of the sodium hydroxide solution is 0.5mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1g:20ml:20ml; (5) Add the pretreated modified bamboo fiber to the prepared carbon nanotube suspension and stir under magnetic force for 12 hours, and obtain the modified bamboo fiber-carbon nanotube composite material after filtration. The amount ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1g:50ml.
[0032] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) preparing a modified bamboo fiber-carbon nanotube composite material according to the above steps; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, modified bamboo fiber-carbon nanotube composite material, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, add the foam stabilizer, and continue to stir the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0033] Example 3 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 20 parts of silica fume, 20 parts of fly ash, 2 parts of foaming agent, 15 parts of fine aggregate, 3 parts of foam stabilizer, 10 parts of modified bamboo fiber-carbon nanotube composite material, 1 part of water reducer, and 130 parts of water.
[0034] The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0035] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0036] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0037] The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing by ultrasonication for 30 min to obtain a carbon nanotube suspension with a concentration of 0.5 wt%; (3) Bamboo fiber and 0.2 mol / L CaCl 2 The solutions were mixed in a ratio of 1g:50ml, stirred at 400r / min for 30min, and then added with equal amounts of Na 2 CO 3 solution, dispersant EDTA-2Na, continue stirring at 300r / min for 25min, after the reaction is completed, rinse with a 200-mesh nylon net under tap water until there are no obvious particles in the suspension, air dry, and obtain modified bamboo fiber; EDTA-2Na and CaCl 2 The dosage ratio of the solution is 0.01g:1ml; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 minutes, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 minutes, taking it out and drying it to obtain pretreated modified bamboo fiber; the concentration of the stearic acid ethanol solution is 2wt%, and the concentration of the sodium hydroxide solution is 0.5mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1g:20ml:20ml; (5) Add the pretreated modified bamboo fiber to the prepared carbon nanotube suspension and stir under magnetic force for 12 hours, and obtain the modified bamboo fiber-carbon nanotube composite material after filtration. The amount ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1g:50ml.
[0038] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) preparing a modified bamboo fiber-carbon nanotube composite material according to the above steps; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, modified bamboo fiber-carbon nanotube composite material, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, add the foam stabilizer, and continue to stir the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0039] Comparative Example 1 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 20 parts of silica fume, 20 parts of fly ash, 2 parts of foaming agent, 15 parts of fine aggregate, 3 parts of foam stabilizer, 10 parts of bamboo fiber, 1 part of water reducer and 130 parts of water.
[0040] The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0041] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0042] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0043] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) Soak the bamboo fiber in 1 mol / L sodium hydroxide solution for 30 min, then take it out and dry it; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, alkali-treated bamboo fiber, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, add the foam stabilizer, and continue stirring the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0044] This comparative example is basically the same as Example 3 except that bamboo fiber is used to replace the modified bamboo fiber-carbon nanotube composite material.
[0045] Comparative Example 2 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 20 parts of silica fume, 20 parts of fly ash, 2 parts of foaming agent, 15 parts of fine aggregate, 3 parts of foam stabilizer, 10 parts of carbon nanotubes, 1 part of water reducer and 130 parts of water.
[0046] The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:1.
[0047] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0048] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0049] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) Mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (2) Mix cement, silica fume, fly ash, fine aggregate, carbon nanotubes, and water reducer in proportion, then add the remaining water, stir at 200 r / min for 10 min, add the foam stabilizer, and continue stirring the slurry for 5 min; (4) The foam obtained in the above step (1) is added to the slurry prepared in step (2), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0050] This comparative example is basically the same as Example 3 except that ordinary carbon nanotubes are used to replace the modified bamboo fiber-carbon nanotube composite material.
[0051] Comparative Example 3 A high-strength crack-resistant foamed concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 20 parts of silica fume, 20 parts of fly ash, 2 parts of foaming agent, 15 parts of fine aggregate, 10 parts of modified bamboo fiber-carbon nanotube composite material, 1 part of water reducing agent, and 130 parts of water.
[0052] The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.3.
[0053] The cement is ordinary Portland cement P·O42.5; the water reducer is polycarboxylate water reducer.
[0054] The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing by ultrasonication for 30 min to obtain a carbon nanotube suspension with a concentration of 0.5 wt%; (3) Bamboo fiber and 0.2 mol / L CaCl 2 The solutions were mixed in a ratio of 1g:50ml, stirred at 400r / min for 30min, and then added with equal amounts of Na 2 CO 3solution, dispersant EDTA-2Na, continue stirring at 300r / min for 25min, after the reaction is completed, rinse with a 200-mesh nylon net under tap water until there are no obvious particles in the suspension, air dry, and obtain modified bamboo fiber; EDTA-2Na and CaCl 2 The dosage ratio of the solution is 0.01g:1ml; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 minutes, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 minutes, taking it out and drying it to obtain pretreated modified bamboo fiber; the concentration of the stearic acid ethanol solution is 2wt%, and the concentration of the sodium hydroxide solution is 0.5mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1g:20ml:20ml; (5) Add the pretreated modified bamboo fiber to the prepared carbon nanotube suspension and stir under magnetic force for 12 hours, and obtain the modified bamboo fiber-carbon nanotube composite material after filtration. The amount ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1g:50ml.
[0055] The specific preparation method of the above-mentioned high-strength crack-resistant foamed concrete is: (1) preparing a modified bamboo fiber-carbon nanotube composite material according to the above steps; (2) mixing a foaming agent and water in a volume ratio of 1:50 to obtain a foaming liquid, and then using an air compressor to pass compressed air into the foaming liquid to form foam; (3) Mix cement, silica fume, fly ash, fine aggregate, modified bamboo fiber-carbon nanotube composite material, and water reducer in proportion, then add the remaining water, stir at a speed of 200 r / min for 10 min, and continue to stir the slurry for 5 min; (4) The foam obtained in the above step (2) is added to the slurry prepared in step (3), and after sufficient stirring, a mixed slurry is obtained. The mixed slurry is poured, demolded and cured to obtain the high-strength and crack-resistant foamed concrete.
[0056] This comparative example is the same as Example 3 except that it does not contain a foam stabilizer.
[0057] Performance Testing Sample: The concrete prepared in Examples 1-3 and Comparative Examples 1-3 was poured into a test mold with a size of 100 mm × 100 mm × 100 mm, and demolded after 24 hours of molding. The demolded sample was placed in a standard curing box with a temperature of (20 ± 2) ° C and a relative humidity of > 95% for 28 days; the dry density (kg / m 3) and 28d compressive strength (MPa), 28d flexural strength (MPa) were measured; thermal conductivity test was carried out in accordance with GB10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method" for transient and flat plate method thermal conductivity test; in accordance with GB / T 50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the crack area of the other five surfaces of the concrete test block except the bottom surface was detected, and the crack area per unit area was calculated. The specific test results are shown in Table 1.
[0058] Table 1 Performance test results As can be seen from Table 1, compared with Comparative Examples 1-3, the foamed concrete prepared in Examples 1-3 has better compressive strength, flexural strength and crack resistance, and also has good thermal insulation performance, and is a high-strength crack-resistant foamed concrete with good comprehensive performance. This is because the modified bamboo fiber-carbon nanotube composite material used in the present invention is mixed with other various raw materials to form a stable three-dimensional network structure inside the concrete, which promotes the uniform distribution of internal bubbles. At the same time, the nano-calcium carbonate therein can also promote cement hydration reaction, refine the crystal form and improve the interface structure of concrete, reduce the pores and cracks in the concrete, reduce the permeability and water absorption of the concrete, and also improve the compatibility and bonding between the fiber material and the cement matrix, thereby better improving the comprehensive performance of concrete crack resistance and compressive strength.
[0059] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A high-strength crack-resistant foamed concrete, characterized in that: It is made of the following raw materials in parts by weight: 200-300 parts of cement, 10-20 parts of silica fume, 10-20 parts of fly ash, 1-2 parts of foaming agent, 5-15 parts of fine aggregate, 1-3 parts of foam stabilizer, 5-10 parts of modified bamboo fiber-carbon nanotube composite material, 0.5-1 part of water reducer, and 120-130 parts of water; The modified bamboo fiber-carbon nanotube composite material is prepared by the following method: (1) distilled water, a silane coupling agent and anhydrous ethanol are uniformly mixed according to a mass ratio to obtain a silane coupling agent solution; (2) adding carbon nanotubes to a silane coupling agent solution and dispersing the carbon nanotubes by ultrasonic for 30 minutes to obtain a carbon nanotube suspension; (3) Mix the bamboo fiber with 0.2 mol / L CaCl2 solution, stir at 400 r / min for a period of time, add equal amounts of Na2CO3 solution and dispersant EDTA-2Na with equal molar concentrations after the reaction, continue stirring at 300 r / min for 25 min, rinse with a 200-mesh nylon net under tap water after the reaction until there are no obvious particles in the suspension, and air-dry to obtain modified bamboo fiber; (4) immersing the modified bamboo fiber in a stearic acid ethanol solution at 75° C. for 30 min, and then immersing the modified bamboo fiber in a sodium hydroxide solution for 30 min, taking it out and drying it to obtain the pretreated modified bamboo fiber; (5) Adding the pretreated modified bamboo fiber obtained in step (4) to the prepared carbon nanotube suspension and subjecting to magnetic stirring for 12 hours, filtering to obtain a modified bamboo fiber-carbon nanotube composite material.
2. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: The mass ratio of distilled water, silane coupling agent and anhydrous ethanol in the silane coupling agent solution is 1:5:50, and the silane coupling agent is KH550.
3. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: The concentration of carbon nanotubes in the carbon nanotube suspension is 0.5 wt %.
4. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: In the step (3), the ratio of bamboo fiber to CaCl2 solution is 1 g:50 ml, and the stirring reaction time is 30 min.
5. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: In the step (3), the ratio of EDTA-2Na to CaCl2 solution is 0.01 g:1 ml.
6. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: In the step (5), the ratio of the pretreated modified bamboo fiber to the carbon nanotube suspension is 1 g:50 ml.
7. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: The foam stabilizer is composed of dodecyl dimethyl amine oxide and polyacrylamide in a mass ratio of 1:
1.
8. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: The foaming agent is composed of plant protein foaming agent FP50A and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.
3.
9. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: In the step (4), the concentration of the stearic acid ethanol solution is 2 wt %, and the concentration of the sodium hydroxide solution is 0.5 mol / L; the usage ratio of the modified bamboo fiber, the stearic acid ethanol solution, and the sodium hydroxide solution is 1 g: 20 ml: 20 ml.
10. The high-strength crack-resistant foamed concrete according to claim 1, characterized in that: The cement is ordinary Portland cement P·O42.5, and the water reducer is polycarboxylate water reducer.
Citation Information
Patent Citations
Rod-like nanometer calcium carbonate modified carbon nano-tube modified carbon fiber reinforced paper-based friction material and preparation method thereof
CN107245901A
Lightweight foam concrete
CN117964305A
Cited By
Low-density thermal insulation foam concrete and preparation method thereof
CN119638485A